Triangle test in sensory analysis: approaches and challenges in the context of proficiency testing - Pinto Manuel; Barros Paulo; Correia Elisete; Vilela Alice (Ciência e Técnica Vitivinícola)
Participation in proficiency testing (PT) programs, as outlined in ISO/IEC 17025, is a vital tool for ensuring the validity of laboratory results. Although it requires an initial investment, the benefits—such as reduced errors, improved efficiency, and the prevention of costly problems—make it a cost-effective approach. This participation enhances accuracy, saves costs, and increases laboratory productivity. The SENSORIAL-ALABE test is designed to enhance tasters’ sensory abilities, offering sensory panels or individual assessors the unique opportunity to track their performance over time confidentially. For this purpose, the triangle test is used, in which three samples are presented to the evaluator in different orders, two of which are identical. The evaluator’s task is to identify the different sample, a process crucial in testing the sensory acuity of the assessor and the group. This method is essential for quantitatively evaluating the response to progressively increasing olfactory stimuli related to defects or aromas in wines and/or wine spirits. The assessor performs the test in four increasing concentrations, identifying the different samples and the compound used based on a table of compounds and sensory descriptors previously established. The results reflect the overall performance of the assessor in the four triangle tests at progressively increasing concentrations, using binomial distribution to assess statistical significance. This study examined the effects of adding a compound to one or two samples to examine whether it influenced participants’ accuracy in identifying the correct samples. Results suggest that adding the compound to two samples generally makes it more challenging for participants to accurately identify the odd sample, leading to more incorrect answers. The proficiency tests show a continuous improvement in the tasters’ performance, especially when they face the same challenge a second time. These tests are essential for constantly improving laboratories performance, enhancing assessors’ sensitivity through training, and providing relevant information for their qualification.